Mitral valve aneurysms: echocardiographic characteristics, formation mechanisms, and patient outcomes - Wang, Yi; Wang, Shuang; Chen, Dandan; Li, Mengmei; Mi, Sulin; Xiong, Li; Song, Wanwan; Wang, Wei; Yin, Shanye; Wang, Bin (Frontiers in Cardiovascular Medicine, 2023)
Background: The exact causes of mitral valve aneurysm (MVA) formation are not fully understood, and the most effective management approach remains controversial. Methods: We conducted a retrospective analysis of 20 patients with MVAs who underwent either surgical interventions or conservative follow-ups at Zhongnan Hospital of Wuhan University between 2017 and 2021. We examined their clinical, echocardiographic, and surgical records and tracked their long-term outcomes.Results: Of the 20 patients, 12 were diagnosed with MVA using transthoracic echocardiography (TTE), while seven required additional transesophageal echocardiography (TEE) for a more definitive diagnosis, and one child was diagnosed in surgery. In all cases, the MVAs were located in the anterior mitral leaflet. We found that 15 patients (75%) were associated with infective endocarditis (IE), while the remaining cases were linked to bicuspid aortic valve and moderate AR and mild aortic stenosis (AS) (5%), congenial heart disease (5%), elderly calcified valvular disease (5%), mitral valve prolapse (5%) and unknown reasons (5%). Of the 17 patients who received surgical interventions, two passed away in hospital due to severe cardiac events. The other 15 patients underwent successful surgeries and were followed up for an average of 13.0 ± 1.8 months. We observed an improvement in their New York Heart Association (NYHA) functional class, degree of mitral regurgitation (MR), and degree of aortic regurgitation (AR) (P value < 0.001). Only one infant experienced an increase in left ventricular end-diastolic diameter (LVEDD) and left ventricular end-systolic diameter (LVESD) during follow-up, while the remaining 14 patients showed a decrease (P value < 0.001). Three patients were managed conservatively, and none of them experienced disease progression during the follow-up period of 7 to 24 months. Conclusions: We recommend using echocardiography as a highly sensitive method for diagnosing MVA. While most cases are linked to IE or AR, there are still cases that require further study to determine their causes. Prompt diagnosis using echocardiography can aid in timely management of MVA patients.